Modelo de gestión de la calidad para mejorar el desarrollo y crecimiento de la Concesionaria Automotríz Autolasa Quevedo, año 2012 - Anastacio Espinoza, Yolanda Rosana (2013)
Quevedo is one of the most progressive cities in the province of Los Rios who has hosted over time an interesting range of immigrants from all regions of the country and abroad. Autolasa is an automotive dealership Galarza Automotive Group belonging to the city of Guayaquil, was incorporated on February 16, 1986. Between 2011 and 2012, annual sales rate decreased to 29.14% annually. The projected yield per salesperson was 79 units by 2012. The bulk of operating expenses are focused on building maintenance absorbing 33.43%. Quevedo applies Autolasa management model known as The Gm Difference, which adopts the same best practices that ensure customer loyalty and ensure that their expectations are being met. The 44.44% of employees considered Autolasa average offices are suitable for the development of activities, while 86.11% are totally dissatisfied with the program of activities, such as sports competitions, workshops, etc. The external field investigation determined that 60.45% of respondents are fully satisfied by the existence of an information board. The 60.45% strongly dissatisfied with the user control in the reception, while the 47.18% strongly dissatisfied with the media to convey their suggestions and opinions. The 88.14% is fully satisfied with the friendly service received when purchasing a vehicle.